1999
DOI: 10.1054/jhsb.1999.0062
|View full text |Cite
|
Sign up to set email alerts
|

The Results of Ulnar Shortening for Ulnar Impaction Syndrome

Abstract: From the Centre tfr Hand Twenty-three wrists in 22 patients (mean age, 37 years) with ulnar impaction syndrome were treated by ulnar shortening. The mean ulnar shortening was 2 mm (range, 1-4 mm). At a mean follow-up time of 33 months, 17 patients had obtained good subjective pain relief and 16 were shown to have a good overall outcome using the Wrightington Hospital Wrist Function Evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
84
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 13 publications
(13 reference statements)
3
84
0
3
Order By: Relevance
“…20,[36][37][38] The disadvantages of ulnar shortening are nonunion/delayed union and hardware irritation. 6,10,15,[17][18][19] However, rates of complication can be low if the procedure is properly performed, 5,38 and many papers have actually reported low complication rates. 31,39 New devices to assist with ulnar shortening osteotomy may further reduce the risk of nonunion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20,[36][37][38] The disadvantages of ulnar shortening are nonunion/delayed union and hardware irritation. 6,10,15,[17][18][19] However, rates of complication can be low if the procedure is properly performed, 5,38 and many papers have actually reported low complication rates. 31,39 New devices to assist with ulnar shortening osteotomy may further reduce the risk of nonunion.…”
Section: Discussionmentioning
confidence: 99%
“…4 This procedure has been the standard treatment for ulnar impaction syndrome for many years. 5,6 Recent biomechanical studies have confirmed that an ulnar shortening osteotomy can improve the stability of the ulnar carpus and distal radioulnar joint (DRUJ). 7,8 As a result, this method is used for the treatment of ulnar-sided wrist pain, a common cause of upper-extremity disability, 2 and has achieved excellent results for posttraumatic TFCC injury and isolated lunotriquetral interosseous ligament (LTIL) tears.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these benefits, ulna shortening osteotomies are historically not without complications and challenges including technical difficulty, risk of nonunion, and painful hardware (and even fractures associated with premature hardware removal) [2,3,6,8,12,18,21,24]. In rationalizing the need for an improved ulna shortening system, Rayhack et al noted excessive healing times and risk of nonunion, imprecise cuts, and "struggles with fixing the osteotomy" as all problems with free-hand techniques [21].…”
Section: Discussionmentioning
confidence: 99%
“…Of the reported complications, painful hardware seems to be the most predominant. Complaints of plate irritation have been found in multiple studies-60% [2], 68% [12], and 100% [24]-often lowering patient satisfaction rates and necessitating a second surgery to remove the plate [3,12] which occasionally resulted in fracture through the osteotomy site [18,24]. This particular problem has led some surgeons to favor the wafer procedure (excision of the distal 2-4 mm of ulna) over extra-articular ulna shortening [6,8].…”
Section: Discussionmentioning
confidence: 99%